How we became wicked - Yates, Alex, 1982- (Atheneum, 2019)
"A viral disease called 'the wickedness' plagues the world, and sixteen-year-olds Astrid and Natalie are two of the only people immune. The girls live in separate, isolated communities, but recent encounters with wicked people link their stories in unexpected ways"--